Botulinum toxin as a therapeutic modality for headache (Research, Society and Development, 2023)
Headache, popularly known as headache, is a common symptom in medical practice that can indicate serious problems. It can manifest itself episodic or continuously, with several associated symptoms, including nausea, vomiting, sensitivity to sensory stimuli, dizziness and irritability. Diagnosis of headache involves a detailed assessment of the patient's history and physical examination, aimed at categorizing the type of headache to determine appropriate treatment. Treatment varies depending on factors such as medical history and pain intensity, and may include a variety of medications. In cases of frequent and debilitating primary headaches, preventive treatment is indicated. Recently, botulinum toxin was approved by ANVISA as a preventive option for migraines when attacks are frequent and impair quality of life. In addition to medicinal options, non-drug approaches such as acupuncture, homeopathy, hypnotherapy and lifestyle adjustments are recommended as preventive measures. Botulinum toxin, derived from the bacteria Clostridium botulinum, is made up of different types, with type A being used to treat migraines. It works by weakening the muscles and providing pain relief, suggesting a direct impact on pain mechanisms. Therefore, the effectiveness of migraine treatment with botulinum toxin is a topic of interest in this study. Therefore, this narrative literature review study aims to analyze the scientific production on the treatment of migraine through the application of botulinum toxin.